Pemanfaatan Limbah Dapur (Telur Ayam Kampung dan Micin) menjadi Pupuk Organik Cair (POC) untuk Tanaman Stroberi: Utilization of Kitchen Waste (Kampung and Micin Chicken Eggs) Into Liquid Organic Fertilizer (POC) for Strawberry Plants - Yasmin Oktaviani; Annissa Mawardini (LPPM Universitas Mataram, 2023)
This study aims to determine the kitchen waste from chicken eggs and micin can be used as POC and POC can fertilize strawberry plants. The method used in this research is the experimental method. In addition, this research was carried out directly by direct observation and carried out in the Belitung area. This study also uses a literature study by reviewing several research results, articles, ebooks, and case studies that occur in the field. The results of this study are: 1) Kitchen waste from free-range chicken eggs and micin can be used as an environmentally friendly and cost-effective liquid organic fertilizer (POC), 2) The results of the application of photosynthetic POC to strawberry plants can fertilize plants and restore soil fertility.